EFFECTIVENESS OF APPLICATION OFAL-ṬARÎQAH AL-INTIQĀ´IYYAH (طريقة الانتقائية) IN LEARNING ARABIC - Dyah Rahmawati (LTN NU Sulawesi Tengah, 2023)
The aim of this research is to determine the process of learning Arabic at SMA Negeri I Dolo and to obtain student learning outcomes in the process of learning Arabic at SMA Negeri I Dolo through al-ṭarῑqah al-intiqā´iyyah. The type of research used by the author is a qualitative research approach which describes in general the effectiveness of implementing al-Ṭarῑqah al-Intiqā´iyyah in Arabic language learning at SMA Negeri I Dolo. Sampling using a questionnaire to strengthen the author's thesis research study. This research describes data in oral and written form sourced from other people and the results of observations of the subjects of this research are educators in the field of study in class XI High School which consists of science and social studies study programs. he results of the research using al-Ṭarῑqah al-Intiqā´iyyah were effective by looking at the final evaluation results: 99% of students completed Arabic subjects, 1% did not. The author concludes that the learning process is very effective, choosing the right method in Arabic language learning activities is a goal that has been set and can be achieved well. The implication of this research is to further improve the quality of Arabic language education so that it is of higher quality and the most important thing is that the students must be able to understand and be able to read and write the al-Qurān.